The ILLEGALITY OF THE PROFILE CLAUSE IN AN INSURANCE CONTRACT (Reflection and Critique Law Magazine, 2020)
A contract is the most common source of obligation, with numerous and immeasurable repercussions in the legal world. It also can be noticed that it is an inflexible branch in its execution, since the agreement of wills once approved becomes law between the parties, and sensitive to addictions, because when signed in bad faith becomes a disorder for those involved. Because of this duality, contracts are constantly the subject of debate in the judiciary. Although the contract figure has several facets, this article will focus on the adhesion contract, used in the profile mode, generally employed by large corporations to formalize the parties' interest in covering a good. Therefore, this article used the bibliographic search as a research method to find the data and raise satisfactory results about this problem. However, the contract based on the driver profile has been generating great discussions, thus, it is intended to analyze the legality of the mentioned clause, seeking to understand the operation of the institute through the bases of Constitutional Law, Civil Law and Consumer Law, besides the most various doctrines that underlie the analysis of legality.